Pengaruh Literasi Keuangan Dan Lingkungan Sosial Terhadap Minat Berinvestasi Saham Syariah (Studi Kasus Pada Mahasiswa Universitas Islam Malang Angkatan 2022) - Siti Mutmainnah; Nurhidayah Nurhidayah; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research is to find out and analyze how financial literacy and social environment influence the interest in investing in Islamic stocks at the Islamic University of Malang. The population in this study were 2022 Non-Faculty of Economics and Business Students of the Islamic University of Malang. This sampling technique uses purposive sampling which is a sample collection technique based on certain criteria with 94 respondents. The analysis technique uses multiple linear regression analysis. The results of this study indicate that financial literacy has a significant effect on the interest in investing in Islamic stocks and the social environment has a significant effect on the interest in investing in Islamic stocks. (Times New Roman; font 12; sentence case, justified, single space, 200 words) Keyword: Financial Literacy, Social Environment, Invesment Interest.